THE ARGENTINE’S LEFT, BETWEEN DICTATORSHIP AND TRANSITION TO DEMOCRACY: NOTES FOR A STUDY - Aguila, Gabriela Beatriz (Revista de Historia Social y de las Mentalidades, 2019)
The article analyzes the Argentine ‘left during the 80s, between the last military dictatorship and transition to democracy. It makes a critical balance about academic studies and proposes some keys for its study, taking into account the impact of the dictatorship on these political associations, the processes of organizational recomposition and the left’s action in the transitional period, from a global perspective on the universe of the Argentine’ left.
Keywords: Left Wing; Argentina; Dictatorship; Transition to Democracy